Proteomic analysis of the mango anthracnose pathogen Colletotrichum gloeosporioides treated with borate highlights distinct mitochondrial response mechanisms. (9th July 2019) - He, S. T.; Chen, T. T.; Xu, X. B.; Zhang, Z. K.; Song, H. C.; Song, H. M.; Meng, L. H.; Zhou, P.; Shi, X. Q.
Abstract : Mango anthracnose caused by the fungal pathogen Colletotrichum gloeosporioides results in substantial economic losses in postharvest fruits. Borate is an effective fungicide against C. gloeosporioides . It appears to induce mitochondrial degradation and dysfunction in the fungal conidia, but the underlying molecular mechanism remains unclear. This study investigated the effects of borate on this pathogen by examining its mitochondrial proteins, which were extracted from C. gloeosporioides mycelium after borate treatment (5 or 10 mm potassium tetraborate for 48 and 72 h) and characterized using proteomic analysis (two‐dimensional electrophoresis, 2‐DE; and mass spectrometry, MS) and bioinformatics. In total, 600 protein spots were separated by 2‐DE, and 115 of these appeared to be differentially expressed proteins (DEPs). Among the DEPs, 58 were identified using MALDI‐TOF‐TOF MS/MS. Borate treatment was found to alter the expression levels of proteins involved in seven different metabolic pathways, mostly related to energy supply and/or biosynthesis. The effect of borate on mRNA expression levels of 17 genes involved in these metabolic pathways was confirmed by real‐time quantitative reverse transcription PCR (qRT‐PCR). The results suggest that borate might have distinct effects on mitochondrial function in C. gloeosporioides and could be used to control anthracnose in postharvest mango fruits.